The Resistance of Lithuania and the West - Kuodytė, Dalia (Genocidas ir rezistencija, 1997)
The very title of the topic defines the object of the research, i.e., the relations of the Lithuanian resistance leaders and leaderships with counterpart resistance organisations in the West. The point is that the direct interest of the diaspora was aligned with the interests of a third party, i.e., the English, American and Swedish intelligence services, and sometimes the latter would prevail. In Lithuania, the pattern was somewhat different, but here too we must inevitably consider the activities of the MGB–KGB in this area, in other words, the specific objectives pursued in this game.